1992
DOI: 10.1111/j.1467-6494.1992.tb00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective Scripts as Organizers of Personal Experience

Abstract: Tomkins's "script theory" was employed for personological inquiry into the ways that individuals organize their experience. This theory posits that individuals' experiences are organized by ideo-affective construals or "scripts." This thesis was examined by first extracting emotional incidents or "scenes" from the autobiographical reports of 10 individuals, and then deriving from these scenes the abstract sequential rules or "scripts" for handling scenes. One month following this assessment, the individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…To know a person well, it is not necessary to have information about all of the different personal scripts and conditional patterns that prevail in all of the different behavioral settings he or she will encounter. Instead, the personologist should seek information on the most salient settings and environments that make up the ecology of a person's life and investigate the most infiuential, most common, or most problematic personal scripts and conditional patterns that appear within that ecology (Demorest & Alexander, 1992).…”
Section: The Problem With Traitsmentioning
confidence: 99%
“…To know a person well, it is not necessary to have information about all of the different personal scripts and conditional patterns that prevail in all of the different behavioral settings he or she will encounter. Instead, the personologist should seek information on the most salient settings and environments that make up the ecology of a person's life and investigate the most infiuential, most common, or most problematic personal scripts and conditional patterns that appear within that ecology (Demorest & Alexander, 1992).…”
Section: The Problem With Traitsmentioning
confidence: 99%
“…For example, McAdams et al (2001) studied contamination scripts (where positive affect is followed by a negative affective outcome) and redemption scripts (where negative affect is followed by a positive affective outcome). More generally, several different investigators have provided empirical support for both the concept of scripts and the process of psychological magnification (Carlson & Carlson, 1984;Demorest, 1995;Demorest & Alexander, 1992;McAdams, Reynolds, Lewis, Patten, & Bowman, 2001;Thorne, 1995), while clinical case studies have also demonstrated the utility of the theory (Carlson, 1981;Magai, 1996 . According to script theory, SDMs are memorial representations that ground narrative sequences of actions, affects, and outcomes in specific autobiographical memories.…”
Section: Self-defining Memories In the Sms Modelmentioning
confidence: 99%
“…In an earlier study, Demorest and Alexander (1992) had raters code individuals' significant personal memories for overarching interpersonal scripts. A month later, these same individuals generated a set of fictional scenarios.…”
Section: Self-defining Memoriesmentioning
confidence: 99%
“…These findings indicate that, as with other types of schemas, personally and emotionally significant scripts influence how newly met experiences are processed. In a previous study, Demorest and Alexander (1992) found this using an idiographic method of script assessment. In their study, participants first wrote autobiographical memories and 1 month later wrote creative stories to a projective task.…”
Section: Discussionmentioning
confidence: 90%